Directive Speech Acts in Vidio.com Indonesian Streaming Television Series Santri Pilihan Bunda by Angling Sagaran - Moh Annur Khoif; Rustono Rustono; Bernadus Wahyudi Joko Santoso (Universitas Negeri Semarang, 2025)
The aim of this research is (1) to explain the types of directive speech acts, (2) to explain the function of directive speech acts, (3) to describe the effect of directive speech acts in the Indonesian streaming television series entitled Santri Pilihan Bunda. Data collection was carried out using the listening method and note-taking technique. Data analysis used pragmatic analysis with pragmatic matching techniques and distribution techniques. The presentation of the results of data analysis used the infotmal method. The results of the study were speech in the Indonesian streaming television series entitled Santri Pilihan Bunda by Angling Sagaran. Based on the type of speech act in directive speech, direct speech acts, indirect speech acts, literal speech acts, and non-literal speech acts were found. Based on the function of directive speech acts, directive functions were found which include the functions of ordering, requesting, prohibiting, advising, inviting, taking action, accusing, criticizing, stating, allowing, rejecting, and conveying. Based on the effect of directive speech acts, the effects of directive speech acts included positive and negative effects. Based on the dominance of the type of directive speech act that was most often found, directive speech acts were indirect speech acts, the dominance of the most common function was the directive speech act of the requesting function and the dominance of the most common effect of directive speech acts was the positive effect.